Core genome phylogenetic analysis of the avian associated Borrelia turdi indicates a close relationship to Borrelia garinii - Margos, G. (2019)
Borrelia burgdorferi sensu lato comprises a species complex of tick-transmitted bacteria that includes the agents of human Lyme borreliosis. Borrelia turdi is a genospecies of this complex that exists in cryptic transmission cycles mainly between ornithophilic tick vectors and their avian hosts. The species has been originally discovered in avian transmission cycles in Asia but has increasingly been found in Europe. Next generation sequencing was used to sequence the genome of B. turdi isolates obtained from ticks feeding on birds in Portugal to better understand the evolution and phylogenetic relationship of this avian and ornithophilic tick-associated genospecies. Here we use draft genomes of these B. turdi isolates for comparative analysis and to determine the taxonomic position within the B. burgdorferi s.l. species complex. The main chromosomes showed a maximum similarity of 93% to other Borrelia species whilst most plasmids had lower similarities. All three isolates had nine or 10 plasmids and, interestingly, one plasmid with a novel partitioning protein; this plasmid was termed lp30. Phylogenetic analysis of multilocus sequence typing housekeeping genes and 113 single copy orthologous genes revealed that the isolates clustered according to their classification as B. turdi. In phylogenies generated from these 113 genes the isolates cluster together with other Eurasian genospecies and form a sister clade to the avian associated B. garinii and the rodent associated B. bavariensis. These findings show that Borrelia species maintained in cryptic ecological cycles need to be included to fully understand the complex ecology and evolutionary history of this bacterial species complex.